The association between type 2 diabetes mellitus, hip fracture, and post-hip fracture mortality: a multi-state cohort analysis - Tebé, C; Martínez-Laguna, D; Carbonell-Abella, C; Reyes, C; Moreno, V; Diez-Perez, A; Collins, G; Prieto Alhambra, D (Springer London, 2019)
Summary Type 2 diabetes mellitus (T2DM) is associated with an excess risk of fractures and overall mortality. This study compared hip fracture and post-hip fracture mortality in T2DM and non-diabetic subjects. The salient findings are that subjects in T2DM are at higher risk of dying after suffering a hip fracture. Introduction Previous research suggests that individuals with T2DM are at an excess risk of both fractures and overall mortality, but their combined effect is unknown. Using multi-state cohort analyses, we estimate the association between T2DM and the transition to hip fracture, post-hip fracture mortality, and hip fracture–free all-cause death. Methods Population-based cohort from Catalonia, Spain, including all individuals aged 65 to 80 years with a recorded diagnosis of T2DM on 1 January 2006; and non-T2DM matched (up to 2:1) by year of birth, gender, and primary care practice. Results A total of 44,802 T2DM and 81,233 matched controls (53% women, mean age 72 years old) were followed for a median of 8 years: 23,818 died without fracturing and 3317 broke a hip, of whom 838 subsequently died. Adjusted HRs for hip fracture–free mortality were 1.32 (95% CI 1.28 to 1.37) for men and 1.72 (95% CI 1.65 to 1.79) for women. HRs for hip fracture were 1.24 (95% CI 1.08 to 1.43) and 1.48 (95% CI 1.36 to 1.60), whilst HRs for post-hip fracture mortality were 1.28 (95% CI 1.02 to 1.60) and 1.57 (95% CI 1.31 to 1.88) in men and women, respectively. Conclusion T2DM individuals are at increased risk of hip fracture, post-hip fracture mortality, and hip fracture–free death. After adjustment, T2DM men were at a 28% higher risk of dying after suffering a hip fracture and women had 57% excess risk of post-hip fracture mortality.